Planck early results XI: calibration of the local galaxy cluster Sunyaev-Zeldovich scaling relations - Ade, Peter A.; Bartelmann, Matthias; Schäfer, Björn Malte (Arxiv, 2011)
We present precise Sunyaev-Zeldovich (SZ) effect measurements in the direction of 62 nearby galaxy clusters (z <0.5) detected at high signal-to-noise in the first Planck all-sky dataset. The sample spans approximately a decade in total mass, 10^14 < M_500 < 10^15, where M_500 is the mass corresponding to a total density contrast of 500. Combining these high quality Planck measurements with deep XMM-Newton X-ray data, we investigate the relations between D_A^2 Y_500, the integrated Compton parameter due to the SZ effect, and the X-ray-derived gas mass M_g,500, temperature T_X, luminosity L_X, SZ signal analogue Y_X,500 = M_g,500 * T_X, and total mass M_500. After correction for the effect of selection bias on the scaling relations, we find results that are in excellent agreement with both X-ray predictions and recently-published ground-based data derived from smaller samples. The present data yield an exceptionally robust, high-quality local reference, and illustrate Planck's unique capabilities for all-sky statistical studies of galaxy clusters.